Photocatalysis: Low Temperature Synthesis of Large‐Size Anatase TiO2 Nanosheets with Enhanced Photocatalytic Activities (Small 48/2017). Issue 48 (19th December 2017) - Tang, Xiao; Chu, Wanyi; Qian, Jueshi; Lin, Jingcheng; Cao, Guozhong
Abstract : In article1701964, Xiao Tang, Guozhong Cao, and co‐workers discover the special microstructure evolution of TiO2 in a 4 °C aqueous solution, from initially aperiodic 2D atom‐networks gradually grown into large‐size anatase nanosheets. The resultant TiO2 nanosheets demonstrate remarkably enhanced photocatalysis and surface activities to spontaneously activate visible light driven photocatalytic reduction.